The CRISPR/Cas9 System Delivered by Extracellular Vesicles - Xinglong Zhu; Mengyu Gao; Yongfeng Yang; Weimin Li; Ji Bao; Yi Li (MDPI AG, 2023)
Clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein (Cas) systems can precisely manipulate DNA sequences to change the characteristics of cells and organs, which has potential in the mechanistic research on genes and the treatment of diseases. However, clinical applications are restricted by the lack of safe, targeted and effective delivery vectors. Extracellular vesicles (EVs) are an attractive delivery platform for CRISPR/Cas9. Compared with viral and other vectors, EVs present several advantages, including safety, protection, capacity, penetrating ability, targeting ability and potential for modification. Consequently, EVs are profitably used to deliver the CRISPR/Cas9 in vivo. In this review, the advantages and disadvantages of the delivery form and vectors of the CRISPR/Cas9 are concluded. The favorable traits of EVs as vectors, such as the innate characteristics, physiological and pathological functions, safety and targeting ability of EVs, are summarized. Furthermore, in terms of the delivery of the CRISPR/Cas9 by EVs, EV sources and isolation strategies, the delivery form and loading methods of the CRISPR/Cas9 and applications have been concluded and discussed. Finally, this review provides future directions of EVs as vectors of the CRISPR/Cas9 system in clinical applications, such as the safety, capacity, consistent quality, yield and targeting ability of EVs.